Análisis del flujo vehicular en las intersecciones semaforizadas del centro de la ciudad de Pasaje - León Pindo, Sonia Zoraida (2017)
The present technical project has the purpose of determining the vehicular flow through the data collected in the study area with the purpose of knowing the vehicular behavior that presents / displays the intersections semaforizadas of Canton Pasaje. Having an efficient vehicular flow is one of the essential factors for the development of a country, a city or a region, reason why some cities of the world have realized studies to reduce the risks that are generated to have a maximum vehicular demand due to the growth population and therefore vehicular, presenting this problem mainly in the intersections for being a point where several lines of flow converge causing conflicts between vehicles or between the vehicle and the pedestrian, ie the difficulty of traffic circulation causes accidents and congestion and even increases noise and pollution. By means of bibliographical revisions related to the subject we include in the document statistical tables and figures of the vehicle composition, the hourly and daily variation of traffic volume of each intersection of study that are obtained by means of the data collection by means of manual gauges during two weeks consecutive for nine hours. In addition, we include the methodological description and the results of the annual average daily traffic study and the application of the Synchro 8 program to optimize traffic flow through traffic light synchronization as a solution measure presented by some countries to control the vehicular flow whose results are a function of the traffic of the hours of maximum vehicular demand that appear in the intersections of the city of Pasaje between the street Bolivar and Ochoa Leon, between the 10 August street and Ochoa Leon and between the street Sucre and Municipality located in Central Park and The 6 Corners between Quito and Bolivar Avenue and the intersection between Quito and Independence Avenue. As a result we have that in the Central Park most cars are followed by motorcycles, light trucks and buses with levels of service A, A and B at intersections, while in the 6 corners mostly cars, motorcycles, buses and light trucks with a level of service at the intersection of B. In addition, the intersection between Bolivar Street and Ochoa Leon and between Quito and Bolivar Avenue are the intersections of greater traffic, presenting at said intersections the maximum hour vehicular demand from 12:00 to 13:00 hours with more than 900 mixed vehicles / hour. Therefore, it is necessary to carry out investigations of the vehicular flow existing in our country with the purpose of giving a solution according to the traffic problems that arise, either by the synchronization of traffic lights or other methods, and to provide a better development to the country, especially in terms of its road infrastructures. In addition, it is recommended that for the quantification of the number of vehicles traveling in the study area to have people trained in the subject and collect the information, especially at the most representative hours of the day. Therefore, considering all these aspects we will have ways to ensure safety to drivers, pedestrians and users of transportation.